Potential of Alborz Province for Eco-tourism Development: a SWOT Analysis - Rezvani, Mohammad Ali (International Journal of Bio-resource and Stress Management, 2023)
In most of the countries tourism is a well developed industry. In Iran, it is possible to develop this industry as natural tourism and eco-tourism. This study examined the natural potential of Alborz province in eco-tourism development by a descriptive analytical method. But Alborz province is facing many challenges in this regard which includes lack of knowledge on tourism; destruction and demolition of constructions of historical importance, and mountains; and waste resulted from tourism. Consequently, awareness about eco-tourism and cooperation of authorities can help in the development of eco-tourism.